STUDY OF FUNDAMENTALS OF ARTIFICIAL INTELLIGENCE IN THE SCHOOL COURSE OF COMPUTER SCIENCE - Valko Наталія; Tynina Ангеліна (Journal of Information Technologies in Education (ITE), 2022)
The article presents the genesis of artificial intelligence as a science aimed at technologies development based on automated highly intelligent systems. Defining the basic concept of "artificial intelligence", the main idea is to teach robotic technology to think intelligently as a person. The factors determined machine intelligence as a global trend, its place in the world market and the prerequisites for the introduction of such technologies in the educational process are considered. Current and future roles of the application in learning are described. New realities require an answer to the question of what education should be today in order to adequately respond to today’s challenges. Possible improvements in teaching students and the benefits of using artificial intelligence programs in education for schools and teachers are presented, analyzed through the prism of learning in computer science lessons. There are sections and typical tasks using AI services. In modern conditions of mixed learning the use of online environments becomes convenient and relevant to perform independent and homework. The example of artificial intelligence learning in a computer science class at school, using the online services is presented. The role of neural systems in this process is shown. They are the most reliable sources in understanding the functioning of artificial intelligence and demonstrate its effectiveness. The research of tools and analysis of the basic conceptual apparatus of artificial intelligence is a tool for using such services in lessons. Modern technologies provide such an opportunity, starting with general secondary education institutions, thus creating an environment for creativity and discovery of individual characteristics of students.